Knowledge and Attitude of Adolescent Students of 11th Grade Aged 15-19 Years Old About HIV/AIDS - Deus, Elisa de; Ribeiro Gonçalves, Mesias; Maria Guterres, Dulce; Tonia Lisboa Dias, Giovania; Evaristo Obeno, Olandino; Soares Amaral, Odelia (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: HIV (Human Immunodeficiency Virus) weakens a person's immunity. AIDS (acquired immunodeficiency syndrome) is a group of symptoms and infections that develop due to weakened immunity caused by HIV. Objective: To understand the knowledge and attitude of 11th grade adolescent students aged 15-19 years old about HIV/AIDS at Colégio São Miguel Arcanjo Vocational High School Method: This research used qualitative descriptive and exploratory approaches. Sample on this research is Female and male students aged 15 19 years old from 11th grade at Colégio São Miguel Arcanjo Vocational High School in Dili who meet the inclusion and exclusion criteria. Result and Discussion: Based on the total number of respondents, 12 people participated in the research, 7 of whom did not have knowledge about HIV/AIDS, and 3 of them had outdated knowledge. Regarding signs and symptoms of HIV/AIDS, only six respondents have no knowledge about the ways of preventing HIV/AIDS. Nine respondents have no experience accessing information about HIV/AIDS in media. Ten respondents said that they are influenced when their friends or colleagues do drugs or have casual sex. Seven respondents have not received information on how to keep a safe distance from HIV/AIDS transmission from their parents or family. Conclusion: Based on the research results, most adolescents lack balanced knowledge about HIV/AIDS.